DIGITAL DETERMINANTS OF NATIONAL ECONOMY RESILIENCE - Alyona Sorokina; Larysa Lebedeva; Tetiana Lositska (Baltic Journal of Economic Studies)
The objective of this research is to ascertain the pivotal factors that exert influence on the resilience of the national economy, employing Ukraine as a case study. The subject of the study is, therefore, the resilience of the national economy. Methodology. In order to outline the theoretical foundations of the study, the methods of theoretical generalisation, historical method and systematisation method were used. The study of the level of digitisation and its impact on economic resilience was based on comparative analysis, systematic and experimental methods. In addition, statistical, index and indicative analysis, as well as graphical and tabular methods were used. Value / Originality. In order to assess economic resilience in the context of digitalisation, a Methodology for Assessing Digital Resilience of the National Economy was developed. The overarching objective of this methodology is to evaluate the digital resilience of the economy in the face of both external and internal pressures. Utilising this methodology, an Integral Index of Digital Resilience for Ukraine was subsequently calculated. Results. The calculations showed that Ukraine has a moderate level of digital resilience. The proposed methodology identified vulnerabilities in the household sector, such as significant disparities in digital literacy among the population, the availability of quality ICT technologies, and the development of legislation on the protection of personal data on digital platforms. In the business sector, the assessment found a strong relationship between the adoption of digital technologies and increased resilience to economic shocks, particularly in the use of ICT technologies and the readiness for further digital development. The assessment of the government sector showed it to be the most resilient, given the existing digital transformations and e-services.